2022
DOI: 10.3390/vaccines10081330
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of High-Dose MVA-Based MERS Vaccine Candidate in Mice and Camels

Abstract: The Middle East respiratory syndrome coronavirus (MERS-CoV) is a zoonotic pathogen that can transmit from dromedary camels to humans, causing severe pneumonia, with a 35% mortality rate. Vaccine candidates have been developed and tested in mice, camels, and humans. Previously, we developed a vaccine based on the modified vaccinia virus Ankara (MVA) viral vector, encoding a full-length spike protein of MERS-CoV, MVA-MERS. Here, we report the immunogenicity of high-dose MVA-MERS in prime–boost vaccinations in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Animal studies provide an important first step in determining the immunogenicity of a virus. Alharbi et al (2022) and van Doremalen et al (2020) found that the MVA-MERS-S and ChAdOx1 MERS vaccines were effective; they boosted antibody titers and prevented viral replication in animal models [27] , [28] . Other than confirming the boost in antibodies, the human studies included in this paper showed that the impact of the vaccine increased as its dosage increased, as there was a significant difference between the high-dose group and the low-dose group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies provide an important first step in determining the immunogenicity of a virus. Alharbi et al (2022) and van Doremalen et al (2020) found that the MVA-MERS-S and ChAdOx1 MERS vaccines were effective; they boosted antibody titers and prevented viral replication in animal models [27] , [28] . Other than confirming the boost in antibodies, the human studies included in this paper showed that the impact of the vaccine increased as its dosage increased, as there was a significant difference between the high-dose group and the low-dose group.…”
Section: Discussionmentioning
confidence: 99%
“…Other than confirming the boost in antibodies, the human studies included in this paper showed that the impact of the vaccine increased as its dosage increased, as there was a significant difference between the high-dose group and the low-dose group. Animal studies will remain an important part of developing a vaccine, given the low number of infections in humans [27] . They also provide more flexibility for examining different doses and frequencies of booster vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this review showed that more geographically representative seroprevalence studies should be conducted, particularly in regions with large camel populations. While our review revealed many publications on the evaluation of vaccine candidates for dromedary camels, advancement is still needed as no licensed animal vaccine is available to date [39, 40].…”
Section: Discussionmentioning
confidence: 99%
“… 176 1 x MVA-MERS-S P/B: MVA-MERS-S Full-length MERS-CoV S glycoprotein (F11L) BALB/c mice Camels P/B: high levels of NAbs in mice and camels. 153 SEVERE ACUTE RESPIRATORY SYNDROME-CORONAVIRUS (SARS-CoV) Homologous or heterologous combinations of NC+MALP-2 (i.n.) and MVA-NC (i.m.)…”
Section: Mva and Nyvac Poxvirus Strains As Vaccine Candidates Against...mentioning
confidence: 99%
“…151 Thus, no specific vaccine or treatment against MERS-CoV is currently available, although several products are under development. 152 Different studies have reported the preclinical 153 and clinical 154 , 155 evaluation of MVA-based vaccine candidates targeting the MERS-CoV spike (S) glycoprotein. In animal models (mice and camels) MVA-MERS-S induced high levels of NAbs with capacity to reduce the transmission of the virus to humans.…”
Section: Mva and Nyvac Poxvirus Strains As Vaccine Candidates Against...mentioning
confidence: 99%